The Influence of the Equity Principle on Undue Influence Doctrine and The Urgency of Its Application in Indonesian Contract Law - ., Ariyanto; Suryo Wicaksono, Lucky (KnE Social Sciences, 2023)
In Indonesia, the concept of undue influence is being used to annul agreements. There is a need to thoroughly analyse the undue influence doctrine, its relationship with the influence of the equity principle, and the urgency of its application in Indonesian contract law because Indonesia does not have a clear defining rule for the term. This study employs normative juridical research techniques by utilising a statutory approach, a case study approach, a historical approach, a comparative approach, and a conceptual approach. In conclusion, the equity principle is crucial when examining excessive influence. Therefore, the doctrine of equity should be considered while formulating the undue impact on the development of favourable legislation in Indonesia. Keywords: Equity Principles, Contract Law, Undue Influence